Basic field management practices of forage seed production - Adie, Aberra; Abdena, Asebe; Bezabih, Melkamu; Mekonnen, Kindu; Assefa, Getnet; Gebreyes, Million (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Forage Seeds Production as a Business Learning workshop. Presentation in Addis, Ababa May 24th-25th, 2022.